Statistical parameters of time series of spring runoff flood of rivers of the Yesil water-economic basin (Journal of Geography and Environmental Management, 2020)
The main characteristics of snowmelt flood runoff of the rivers of Yesil water-economic basin (dates of spring flood: starting date of flood, peak date flood end and date flood duration). The nonstationarity of the long-term series of characteristics of the spring flow of the rivers of the Yesil basin and the revealed changes in the water regime are caused by climatic factors. Analysis of initial information on flow and characteristic dates for the flood flow shows the presence of directional changes at time series of separate flow characteristics for the period from 1970 to 1990, what was the main reason for the inhomogeneity of the time series. The distribution curves are used in the calculations of statistical parameters and values of flow of different security: Kritsky-Menkel and Pearson type III distribution (for homogeneous series) and composite distribution curves (for inhomogeneous series). Trends in changes in the spring flood runoff characteristics are analyzed and the parameters of the curves of maximum water flow and runoff layers in the Yesil river basin are calculated (long-term data on 42 hydrological posts of the water basin are used).The results show that changes in the statistical parameters of the highest waters in the Yesil river basin are influenced by anthropogenic factors, and the average shifts in their passage time are due only to the influence of climate change.
Keywords: characteristics of the spring flood, the flood, the volume of flow, the sum total layer runoff spring for the flood, maximum water flow, the module of the maximum runoff for spring floods, long-term changes of the maximum runoff of spring floods.